Exploring learning methods in tutoring to enhance students' learning outcomes - Iwan Darmawan; Dzulfikri Dzulfikri; Anisa Zuhria Sugeha (EnJourMe (English Journal of Merdeka) : Culture, Language, and Teaching of English, 2023)
Non-formal education can be obtained when students take tutoring. Tutoring can be defined as an activity outside of school. The purpose of this research is to find out (1) the effect of tutors on learning outcomes, (2) the effect of learning models on learning outcomes, and (3) the simultaneous effect of tutors and learning methods on learning outcomes. The researchers took a sample of 80 students in grade 12 who were spread across Malang and studied at the same tutoring. The sampling method was random sampling. Data collection tools using Likert scale questionnaire. The data analysis technique used the quantitative description. Based on the calculation, several things are obtained, 1) Tutors have no significant effect on student learning outcomes. 2) Learning methods significantly affect student learning outcomes. 3) Tutors and learning methods simultaneously influence each other. It can be concluded that learning methods have a significant effect on learning outcomes. There are many learning methods used, one of which is discussion. Discussion is an appropriate learning method if used in tutoring.